The Effect of Benzo (A) Pyrene (BaP) On the Respiratory Tract of Dogs - Hamzah, Hazilawati (2000)
The global impact of air pollution encompasses the population health and the economic status of a nation. Air pollution or 'haze' contains a variety of noxious agents including benzo(a)pyrene (BaP). This compound is known to induce acute or chronic deleterious effects. The objectives of the study were to determine the effect of BaP on the physiology, defense mechanism and pathology of the lung, to suggest sensitive diagnostic techniques for the diagnosis of early carcinogenesis and to recommend preventive measures to minimise the effect of BaP. An experiment was conducted in 27 dogs that are allocated to nine groups simulating different environmental condition and health status. The groups comprising of three dogs each were as follows: control, BaP, cyclosporine (Cyclo), Selenium (Se), BaP+Cyclo, BaP+Se, BaP+Cyclo+Se and Tricaprylin (Tri). Benzo(a)pyrene was given at the dose of 120 ng/dog intratracheally twice, six week apart, Se 20 ug/dog/day and cyclosporine at the dose 50 mg/m2. The tidal volume (Vt) and whole blood glutathione peroxidase (GSH-PX) activity was analysed weekly for 12 weeks. While at necropsy, bronchoalveolar lavage (BAL) cytology, alveolar macrophage (AM0) activities, BAL immunoglobulin (Ig) G and Ig A level, gross and histopathology of lungs were also analysed. The finding revealed that the tidal volume (Vt) remain unchanged in all groups during the experimental period. The pulmonary immune response includes AM0 number, phagocytic and intracellular killing activities, and Ig A level in bronchoial alveolar lavage (BAL) that was markedly suppressed in the BaP, Cyclo and BaP+Cyclo groups. Subsequently, the BaP and BaP+Cyclo+Se group exhibited gross and microscopic appearance of tumorigenesis, which was diagnosed as pulmonary adenocarcinoma with expression of mutant p53 protein while the BaP+Cyclo and BaP+Se had atypical adenomatous hyperplasia (AAH). Based on the finding, exposure to BaP can lead to pulmonary immuno-suppression and tumorigenesis in dogs. It is also showed that during haze episode, immuno-stressed individuals are more prone to the development of pulmonary immuno-suppression and tumorigenesis. Selenium supplementation or cyclosporine has great potential in combating these deleterious effects. However, simultaneous supplementation of Se together with cyclosporine during haze is not advised, since this will promote tumorigenesis in the lung. In conclusion, intratracheal instillation (twice, six week apart) of 120 llg BaP/dog causes insignificant reduction of Vt, pulmonary immunosuppression and pulmonary carcinogenesis. The immunocytochemical detection of p53 can be used as a sensitive diagnostic technique for the diagnosis of early pulmonary carcinogenesis. Daily oral administration of Se as a supplement has great potential in minimising the adverse effect of BaP.